Single‐Molecule Interaction of Peptides with a Biological Nanopore for Identification of Protease Activity. Issue 11 (5th May 2020) - Sun, Ke; Ju, Yuan; Chen, Chuan; Zhang, Peng; Sawyer, Erica; Luo, Youfu; Geng, Jia
Abstract: The facile and sensitive detection of peptides is essential for drug screening, pathogen detection, and protein sequencing. There are still challenges for the real‐time single‐molecule sensing and detection of peptides due to their versatile shape, structure, and charges brought by amino acids. Nanopore sensing is an emerging technology for sensing of biomolecules including DNA, RNA, and proteins. In this study, the interaction between peptides of different lengths (N6–N10) and charges with an engineered Mycobacterium smegmatis porin A nanopore are systematically studied, and two types blockage events can be identified by quantifying their dwell times and amplitude of blockades. The findings are further applied to the label‐free and real‐time quantification of protease activity of caseinolytic protease P at nanomolar concentration in 14 min. The protease activity with inhibitor can also be monitored real time by nanopore assay. In summary, this nanopore‐based sensing platform shows promising capacity for peptide detection, protease activities assay, and inhibitor screening. Abstract : The engineered nanopore Mycobacterium smegmatis porin A is used to identify negatively charged peptides with varying length, and an efficient, label‐free, and real‐time detection method of nanomolar caseinolytic protease P protease activity is developed by measuring the quantities of remaining substrate, which is further verified by inhibitor AV170.